Clinical Effectiveness and Safety of X-ray- or C-arm-Guided Acupotomy for Spinal Disorders: A Systematic Review - NamDo An; Seojin Bang; DongKun Ko; Hanju Kang; Hyunwoo Jee (Journal of Korean Medicine, 2026)
Objectives: This study aimed to systematically review the current evidence on the clinical effectiveness and safety of X-ray- or C-arm-guided acupotomy for spinal disorders.Methods: PubMed, CNKI, and RISS were searched for studies published from January 2000 to April 6, 2026. Clinical studies evaluating X-ray-, C-arm-, or fluoroscopy-guided acupotomy for spinal disorders were included. Reviews, case reports, theses, conference abstracts, animal studies, studies using ultrasound or CT guidance alone, and studies without extractable quantitative outcomes were excluded. Risk of bias was assessed using RoB 2.0, ROBINS-I, and the NIH before-and-after study assessment tool, and findings were narratively synthesized. The review was registered in the Research Registry (reviewregistry2105).Results: Nine studies involving 707 participants were included: five randomized controlled trials, two non-randomized comparative studies, and two single-arm before-and-after studies. The included studies evaluated cervical radiculopathy due to cervical spondylosis, cervical spondylosis, lumbar disc herniation, and lumbar facet joint-related low back pain. Most studies reported improvements in pain, functional outcomes, or overall treatment response after X-ray- or C-arm-guided acupotomy. However, study designs, interventions, comparators, outcomes, and follow-up periods were heterogeneous, and adverse events were insufficiently reported.Conclusions: X-ray- or C-arm-guided acupotomy may be associated with pain reduction and functional improvement in spinal disorders. However, the certainty of current evidence remains limited because of methodological heterogeneity and insufficient safety reporting. Further high-quality randomized controlled trials with standardized protocols and systematic adverse-event reporting are needed.